ECONOMIC EFFICIENCY OF FISHING AMONG MARINE AND LAGOON ARTISANAL FISHERFOLKS IN LAGOS STATE, NIGERIA (2014)
Fishing is a major source of livelihood for rural and peri-urban communities along coastal waters. The operation of artisanal fisherfolks is threatened by increasing overfishing of inshore waters, inadequate credit facilities, insufficient fishing input subsidies and inadequate extension services. These had negative implications on their efficiency hence their well-being. In order to enhance their performance, the efficiency of the fisherfolks, profitability and challenges were examined, as empirical information on these was scanty. A multistage sampling technique was used. Thirty-six communities comprising of eighteen marine and eighteen lagoon communities were selected from 110 communities containing 3,621 fisherfolks farm families in the village listing survey reports of Lagos State Agricultural Development Authority. Ten fishing households were randomly selected per community. Data were collected through the use of structured questionnaire on fishers‟ socio-economic characteristics, input and output (Technical Efficiency TE), their prices (Allocative Efficiency AE). Economic Efficiency (EE) was measured as a product of AE and TE. Data were analysed using Descriptive statistics, Gross margin analysis Income-Expenditure ratio, stochastic production and cost frontier model at p = 0.05. Male fishermen dominated the Marine and Lagoon marine and lagoon operations (100%, 93.9%) respectively. The average household for the marine (6-9) was higher than that of the lagoon (2-5). The mean age of fisherfolks was 43.0 + 8.18 years; with 7.2% and 20.0% of marine and lagoon fisherfolks within the age range of 30-40 years respectively.Constrains experienced by marine and lagoon fisherfolks include stormy weather (75.0%, 80,8%), severe water turbulence (76.0%, 90.0%) capsizing of canoe (91.0%, 58.0%), high cost of input (65.0%, 84.0%), lack of credit (34.6%, 88.8%) and high interest rate (38.2%, 86.3%) respectively. Gross Margin for the marine household (N61,000.77+9,35U9) was significantly higher than lagoon (N27,973.01±2,563.14). Benefit-cost ratio was 3.2 for marine and 2.5 for lagoon. Coefficients of: labour (1.71), size of canoe (0.33), distance covered, (0.90), and capacity of outboard engine, (0.16) significantly increased the quantity of fish caught. However, none of the variables was significant for lagoon frontier model. Technical Efficiency indices ranged from 56.0% - 83.0% for marine and 51.0% - 83.0% for lagoon. The mean T.E for marine (0.73) was greater than that of lagoon (0.68). Allocative efficiency indices ranged from 38.6% - 86.0% and EE indices ranged from 4.0% - 72.0% among the fisherfolks. Among marine and lagoon operations, coefficients of age (-0.25, -0.18), secondary income (-0.01, -0.01), were negatively related and significantly reduced technical inefficiency while coefficient of canoe type (-0.19, -0.16), and gear type (-0.18, -0.09) were negative and significantly reduced Allocative and Economic inefficiency respectively. Marine fisherfolks operation was more efficient than lagoon. However, involvement of aged fishermen in fishing, engagement of most fishermen in secondary occupation decreased efficiency. Capacity of outboard engine, distance covered and size of labour influenced quantity of fish caught by marine fisherfolks